Antibacterial porous sponge fabricated with capric acid-grafted chitosan and oxidized dextran as a novel hemostatic dressing. (1st February 2022) - Wang, Xiaoyu; Dang, Qifeng; Liu, Chengsheng; Chang, Guozhu; Song, Hao; Xu, Qing; Ma, Yue; Li, Boyuan; Zhang, Bonian; Cha, Dongsu
Abstract: This work aims to fabricate multifunctional hemostatic sponges (C-ODs). Porous C-ODs were first constructed by using capric acid-modified chitosan (CSCA) and oxidized dextrans (ODs) with different oxidation degrees. Batches of experiments showed that (i) CSCA (33.39% of grafting degree), ODs, and C-ODs (100–200 μm in pore size) were synthesized, evidenced by FT-IR, 1 H NMR, elemental analysis, hydroxylamine hydrochloride titration, and SEM results; (ii) among C-ODs, C-OD2 had appropriate porosity (85.0%), swelling (20 times its dry weight), absorption, water retention, water vapor transmission, and mechanical properties; (iii) C-OD2 possessed low toxicity (relative cell viability > 86%), low hemolysis rate (0.65%), suitable tissue adhesion (4.74 kPa), and strong antibacterial efficacy (five strains); and (iv) C-OD2 's dynamic blood clotting was within 30 s. In three animal injury models, C-OD2 's hemostasis time and blood loss were fairly lower than commercial gelatin sponge. Totally, C-OD2 might serve as an ideal hemostatic dressing. Graphical abstract: Unlabelled Image